Accessing the online evidence: a guide to key sources of research information on clinical and cost effectiveness. Issue 3 (1st June 2003) - Glanville, J; Wilson, P; Richardson, R
Abstract : Advice on how to access the best available online sources of research evidence on clinical and cost effectiveness published in three recent issues of Effectiveness Matters is reviewed.